Vaccine-derived poliovirus surveillance in China during 2001–2013: the potential challenge for maintaining polio free status - Hai-Bo Wang (BMC Infectious Diseases, 2017)
Abstract Background The goal of polio eradication is to complete elimination and containment of all wild, vaccine-related and Sabin polioviruses. Vaccine-derived poliovirus (VDPV) surveillance in China from 2001–2013 is summarized in this report, which has important implications for the global polio eradication initiative. Methods Acute flaccid paralysis (AFP) cases and their contacts with VDPVs isolated from fecal specimens were identified in our AFP surveillance system or by field investigation. Epidemiological and laboratory information for these children were analyzed and the reasons for the VDPV outbreak was explored. Results VDPVs were isolated from a total of 49 children in more than two-thirds of Chinese provinces from 2001–2013, including 15 VDPV cases, 15 non-polio AFP cases and 19 contacts of AFP cases or healthy subjects. A total of 3 circulating VDPVs (cVDPVs) outbreaks were reported in China, resulting in 6 cVDPVs cases who had not been vaccinated with oral attenuated poliomyelitis vaccine. Among the 4 immunodeficiency-associated VDPVs (iVDPVs) cases, the longest duration of virus excretion was about 20 months. In addition, one imported VDPV case from Myanmar was detected in Yunnan Province. Conclusions Until all wild, vaccine-related and Sabin polioviruses are eradicated in the world, high quality routine immunization and sensitive AFP surveillance should be maintained, focusing efforts on underserved populations in high risk areas.